PEMBENTUKAN KARAKTER ANAK GEMAR MEMBACA MELALUI PEMBACAAN BUKU CERITA - Saepudin, Encang; Agustini Damayani, Ninis; Komariah, Neneng (BACA: Jurnal Dokumentasi dan Informasi, 2020)
This study aims to determine the process of building children's character who likes reading through reading story books. The research objectives are knowing the storytelling process and the benefits of storytelling in building the character of children who love reading. Qualitative research methods with a case study approach. The source of research data is one community leader, two managers of the Taman bacaan Permata Hati, and one person from the education office. Collecting data through interviews with key informants, direct observation of research objects, and literature studies. Test the validity of the data through triangulation. Descriptive data analysis through stages of reduction, presentation, and drawing conclusions. The results showed that the storytelling process to build the character of children who love reading is to set goals, form of storytelling, supporting facilities, storytelling steps, and assessment design.